Research Status on Microstructure and Localized Corrosion Resistance of Ferrite/Austenitic Duplex Stainless Steels - ZHANG Zhi-qiang, JING Hong-yang, XU Lian-yong, ZHANG Tian-gang, Xu Yu-tong, Bai Yu-jie (Cailiao Baohu)
Ferrite/austenite duplex stainless steel(DSS)has a unique microstructure, a combination of high strength, good ductility and toughness, and excellent resistance to localized corrosion.Compared with austenitic stainless steel and nickel-based alloy with the higher nickel content, the DSS saves a scarce resource of nickel in China, which, therefore, presents a wide application prospect in many national key energy fields such as marine engineering, petrochemical, and nuclear power.In this paper, the research progress of DSS microstructure was discussed from several aspects including the phase transformation, texture, orientation relationship, and boundary characteristic of ferrite and austenite as well as secondary phases.After that the research statuses of DSS localized corrosion resistance was reviewed.Finally, the existing problems and future development of DSS were put forward.